Biophysical and computational characterization of vandetanib–lysozyme interaction - Kabir, Md Zahirul; Hamzah, Nur Aziean; Ghani, Hamidah; Mohamad, Saharuddin; Alias, Zazali; Tayyab, Saad (Elsevier, 2018)
Interaction of an anticancer drug, vandetanib (VDB) with a ligand transporter, lysozyme (LYZ) was explored using multispectroscopic techniques, such as fluorescence, absorption and circular dichroism along with computational analysis. Fluorescence data and absorption results confirmed VDB–LYZ complexation. VDB-induced quenching was characterized as static quenching based on inverse correlation of KSV with temperature as well as kq values. The complex was characterized by the weak binding constant (Ka = 4.96–3.14 × 103 M−1). Thermodynamic data (ΔS = + 12.82 J mol−1 K−1; ΔH = − 16.73 kJ mol−1) of VDB–LYZ interaction revealed participation of hydrophobic and van der Waals forces along with hydrogen bonds in VDB–LYZ complexation. Microenvironmental perturbations around tryptophan and tyrosine residues as well as secondary and tertiary structural alterations in LYZ upon addition of VDB were evident from the 3-D fluorescence, far- and near-UV CD spectral analyses, respectively. Interestingly, addition of VDB to LYZ significantly increased protein's thermostability. Molecular docking results suggested the location of VDB binding site near the LYZ active site while molecular dynamics simulation results suggested stability of VDB–LYZ complex. Presence of Mg2+, Ba2+ and Zn2+ was found to interfere with VDB–LYZ interaction.